Early-Life Respiratory Infections in Infants with Cow’s Milk Allergy: An Expert Opinion on the Available Evidence and Recommendations for Future Research - Alessandro Fiocchi (MDPI AG, 2021)
Acute respiratory infections are a common cause of morbidity in infants and young children. This high rate of respiratory infections in early life has a major impact on healthcare resources and antibiotic use, with the associated risk of increasing antibiotic resistance, changes in intestinal microbiota composition and activity and, consequently, on the future health of children. An international group of clinicians and researchers working in infant nutrition and cow’s milk allergy (CMA) met to review the available evidence on the prevalence of infections in healthy infants and in those with allergies, particularly CMA; the factors that influence susceptibility to infection in early life; links between infant feeding, CMA and infection risk; and potential strategies to modulate the gut microbiota and infection outcomes. The increased susceptibility of infants with CMA to infections, and the reported potential benefits with prebiotics, probiotics and synbiotics with regard to improving infection outcomes and reducing antibiotic usage in infants with CMA, makes this a clinically important issue that merits further research.